Utility Klasifikasi Kata Berdasarkan Kamus pada Dokumen Bertipe Word (.docx) Berbasis Web - Dwi Sakethi; Raka Widharma Kartika (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Word class is one of the central aspects in Indonesian grammar. To understand the classification of word classes, it is less effective to do the it manually. So, developing a tool that can help fasten the process of classifying word classes in the document is need. Therefore, this research aims to build a system that can help make it easier for users to minimize time and human resources in determining the word class of a text document itself. The research development of a word classification system based on a dictionary on a word document (.docx) using the Waterfall or Classic Life Cycle, is divided into several stages, namely requirements specification and analysis, system and software design, coding and unit testing, system integration and testing, and installation and maintenance. This study resulted in a word classification system based on a dictionary on a word document (.docx). The success obtained in the development of this system is evidenced by the statistical data that shows the level of user satisfaction with a total average of 88.35% which is in the